An incremental version of iterative data flow analysis - Pollock, L.L.; Soffa, M.L. (IEEE transactions on software engineering, 1989)
A technique is presented for incrementally updating solutions to both union and intersection data-flow problems in response to program edits and transformations. For generality, the technique is based on the iterative approach to computing data-flow information. The authors show that for both union and intersection problems, some changes can be incrementally incorporated immediately into the data-flow sets while others are handled by a two-phase approach. The first phase updates the data-flow sets to overestimate the effect of the program change, enabling the second phase to incrementally update the affected data-flow sets to reflect the actual program change. An important problem that is addressed is the computation of the data-flow changes that need to be propagated throughout a program, based on different local code changes. The technique is compared to other approaches to incremental data-flow analysis.< >